ChemInform Abstract: 4‐Hydroxy‐1‐phenylquinolin‐2(1H)‐one in One‐Pot Synthesis of Pyrimidoquinolines and Related Compounds under Microwave Irradiation and Conventional Conditions. Issue 31 (14th July 2016) - Mourad, Aboul‐Fetouh E.; Amer, Amer A.; El‐Shaieb, Kamal M.; Ali, Ali M.; Aly, Ashraf A.
Abstract: The title compound is utilized in Biginelli condensation reactions with aryl aldehydes and urea, or thiourea, triazole, and benzimidazole.